2018
DOI: 10.1186/s12970-018-0218-y
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine for sports: a review

Abstract: The use of herbal medicinal products and supplements has increased during last decades. At present, some herbs are used to enhance muscle strength and body mass. Emergent evidence suggests that the health benefits from plants are attributed to their bioactive compounds such as Polyphenols, Terpenoids, and Alkaloids which have several physiological effects on the human body. At times, manufacturers launch numerous products with banned ingredient inside with inappropriate amounts or fake supplement inducing harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 115 publications
(138 reference statements)
3
106
0
21
Order By: Relevance
“…Meanwhile, 6-minute walking test is a gold indicator for assessing cardiopulmonary functions by test activity tolerance. Qi is considered to be the most essential substance in human beings, directly reflecting life activities and activity tolerance, and Astragalus is one of the first choices for Qi in TCM theory, especially good at relieving fatigue and improving activity tolerance [49]. In this study, Astragalus injection can reduce the mortality and increase the distance of 6-minutes walking test of patients with Zong Qi depression, which is in line with the theory of traditional Chinese medicine.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 65%
“…Meanwhile, 6-minute walking test is a gold indicator for assessing cardiopulmonary functions by test activity tolerance. Qi is considered to be the most essential substance in human beings, directly reflecting life activities and activity tolerance, and Astragalus is one of the first choices for Qi in TCM theory, especially good at relieving fatigue and improving activity tolerance [49]. In this study, Astragalus injection can reduce the mortality and increase the distance of 6-minutes walking test of patients with Zong Qi depression, which is in line with the theory of traditional Chinese medicine.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 65%
“…45 Gingerols are potent vanilloid receptor (VR1) agonists which may in part explain ginger's analgesic effects. 13 In human studies, the positive effect of intake of ginger on pain has shown in athletes 49,50 and in women with dysmenorrhea. 51 In particular, regarding dysmenorrhea, it has been shown that ginger is as effective as mefenamic acid and ibuprofen on pain relief in primary dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng as an endurance performance enhancer. [ 48 ] Currently there are no recommendations or guidelines on use of such substances in sports. Hence it is very much necessary to know pharmacology of different drugs.…”
Section: R Ole and I Mportance Of mentioning
confidence: 99%